The Influence Of Competence And Job Placement On Employee Performance In The General Secretariat Of The Regional Secretariat Of Lampung Central Regency - Hudalil, Ahmad; Junizar, Junizar (Utami Publisher, 2025)
The phenomenon that occurs in the General Section of the Regional Secretariat of Central Lampung Regency regarding employee competency is that there is still a shortage in increasing the knowledge, expertise and skills of Civil Servants, considering that there are no spending activities for technical guidance and special training according to the field of work they are involved in. The elimination of spending on technical guidance and special training was due to the results of the Provincial Government's evaluation being one of the things that hinders Civil Servants in the General Section from participating in education and training that is useful in improving their competence. In terms of job placement for Civil Servants, it is still not based on the educational background they have mastered and until now its implementation has prioritized filling deficiencies rather than fulfilling the required qualifications. The problem of competency and work placement factors, as described above, is seen as one of the causes of the performance conditions of Central Lampung Regional Secretariat General Section employees which are not yet optimal. The aim of this research is to determine the effect of competency and work placement on employee performance. The hypothesis in this research is that there is an influence of competence and work placement, both partially and simultaneously, on employee performance.The sample used in this research was 36 employees. Data collection techniques include documentation and distribution of questionnaires to respondents. The data analysis method uses a quantitative approach with the help of SPSS version 21.0 statistical tools including calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and coefficient of determination tests.The results of partial hypothesis testing of the influence of competence on performance show that competence has a positive effect on employee performance with a contribution of 50.6%. Employee placement has a positive effect on employee performance with a contribution of 41.3%. Simultaneous hypothesis testing shows that competence and work placement together have a positive effect on employee performance with a contribution of 54.6%, while the remaining 45.4% is the influence of other variables outside this research.